Análisis De Alternativas De Paso Sobre El Río Soacha Para La Carrera 11 Con Calle 18 Del Municipio De Soacha (2022)
This document contemplates different alternatives of passage on the Soacha River for the 11th and 18th Street in the municipality of Soacha. For the development of this it was necessary to draw some basic objectives that were the pillars of this work, the main objective was to identify the need for the community to have a crossing that would allow to communicate two parts of Soacha divided by the river, where in a distance of approximately 2 kilometers, there are currently only two road crossings where vehicles circulate in one lane but in both directions and are in very bad condition. Another crossing is a pedestrian crossing that was built by the community and where this work is focused. Based on the conceptual engineering and information collected, a solution to this problem is proposed, which consists in the creation of a bridge with the characteristics proposed by the document: construction of vehicular Bridges on secondary or tertiary roads of invias, from where the basic design parameters are extracted as the light of the bridge and a budget for the proposed prototype; This work and its respective research allows us to contemplate the multiple possibilities and the advances that have been made for the construction of sustainable structures, but it is very difficult to apply them due to the lack of regulations, political will and civic culture, therefore we resort to a conventional structure but clearly functiona